Analysis study of hybrid Caputo-Atangana-Baleanu fractional pantograph system under integral boundary conditions - Thabet, Sabri T. M.; Kedim, Imed; Samei, Mohammad Esmael; Abdeljawad, Thabet (Mathematical Modelling and Analysis, 2025)
This manuscript investigates the qualitative analysis of a new hybrid fractional pantograph system involving AtanganaBaleanu-Caputo derivatives, complemented by hybrid integral boundary conditions. Dhage’s fixed point theorem is employed to investigate the existence theorem of the solutions, while uniqueness is proven by using Perov’s approach and Lipschitz’s matrix. The Hyers-Ulam (HU) stability is also demonstrated using the Lipschitz’s matrix and techniques from nonlinear analysis. Finally, illustrative example is enhanced to examine the effectiveness of the obtained results.